Implementation of the “CANTIK” (Preventing Anemia with Acupressure Techniques and Consuming Blood Supplement Tablets) in Adolescent Girls to Prevent Stunting - Rastiti, Ida Ayu Anom; Strisanti, Ida Ayu Suptika (Babali Publisher, 2025)
Introduction: The study explores the connection between anemia in adolescent girls and the risk of stunting in their future children. To prevent this, researchers developed the CANTIK program, which combines acupressure techniques and iron supplementation. The aim is to evaluate the program's effectiveness in improving hemoglobin levels and preventing anemia in adolescent girls. Method: A pre-experiment with a one-group pretest-post-test design was conducted to evaluate the effect of acupressure and blood supplement tablets on hemoglobin levels. The study involved 33 second-year adolescent girls from SMAN 3 Denpasar, selected through stratified random sampling from 149. Participants met the criteria of having menstruation and being healthy. Hemoglobin levels were measured before and after the one-month intervention using a hemoglobin meter, with results analyzed using a paired t-test. Result: The average age of participants was 16, with most having a normal BMI (54.40%), not being at risk of chronic energy deficiency (72.70%), and having regular (81.82%) and normal-length periods (93.94%). The study showed a significant increase in hemoglobin levels from pre-intervention (Mean = 11.60, SD = 1.27) to post-intervention (Mean = 12.51, SD = 1.11) with a p-value of 0.001. The mean increase was 0.97, with a 95% confidence interval. Additionally, compliance with blood supplement tablet consumption rose from 0% to 97.0% after one month. Conclusion: Blood supplement tablet consumption and acupressure significantly increased adolescent girls' hemoglobin levels. Applying acupressure as a complementary therapy to increase hemoglobin levels is highly recommended.